Determinants of Community Health Center Performance: The Mediating Role of Employee Performance - Ainul Fadilah; Sulis Diana; Yusuf Alamudi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Community Health Centers are the cornerstone of primary healthcare and play a vital role in meeting regional Minimum Service Standards. A decline in SPM achievement at the Mojokerto District Health Office in 2024—specifically in regional technical implementation unit (RTIU) Community Health Centers Sooko and Jetis—indicates challenges in maintaining service quality, strongly related to employee performance. This study Aim is to analyzes the influence of individual factors (ability and motivation) and organizational factors (workload and compensation) on Puskesmas performance, with employee performance as an intervening variable. A cross-sectional quantitative approach was used, involving 96 civil servants from both Community Health Centers units through total sampling. Data collection in this study is primary data and secondary data, secondary data in this study include: health center performance, employee performance, ability, motivation, workload and compensation by using a Likert scale. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was applied for analysis. The results of the study show that significant positive effects of: Ability (Sooko: β = 0.218, p = 0.020; Jetis: β = 0.234, p = 0.013), Motivation (Sooko: β = 0.311, p = 0.006; Jetis: β = 0.198, p = 0.025), Workload (Sooko: β = 0.216, p = 0.004; Jetis: β = 0.164, p = 0.007), Compensation (Sooko: β = 0.246, p = 0.004; Jetis: β = 0.249, p = 0.007) on employee performance. Employee performance also significantly affected institutional performance (Sooko: β = 0.312, p = 0.000; Jetis: β = 0.275, p = 0.000). Although indirect effects were not statistically significant, they still contributed positively. The findings underscore the need to strengthen human resource management—through capability development, motivation enhancement, workload balance, and fair compensation—to improve public health service outcomes.